Cultivating digital agriculture, a collaborative approach to extension and education - Ramos, Gresia Dalal; Jimenez, Daniel Ricardo; Martinez, Jesus David; Lizarazo, Miguel; Bonilla, Melissa; Munoz, Luis Armando (2024)
Since 2022, a total of 84 professionals from Guatemala and Colombia have graduated from diploma programs focused on digital agriculture and sustainability, enhancing regional food security and climate resilience. In Guatemala, 52 graduates completed three programs: 26 from the Digital Agriculture Diploma in 2022, 9 from Innovative Extension Services in 2023, and 17 CUNORI faculty members from Digital Tools for Research in 2024. These programs have also contributed to the creation of the Digital Plot at CUNORI, an innovative space integrating advanced technologies for learning, exploration, and technology validation in the agri-food sector. Inspired by these efforts, in Colombia, Universidad ICESI replicated these efforts in 2024 with two cohorts of the Digital Agriculture Diploma course, graduating 32 professionals. Across Guatemala and Colombia, digital agriculture formed the backbone of the curriculum, tailored to meet agricultural needs. Together, these efforts are equipping the next generation of agricultural professionals with the skills to harness digital tools to address challenges while enhancing CGIAR partners’ capacity to design and implement inclusive digital solutions